Influenza hospitalization epidemiology from a severe acute respiratory infection surveillance system in Jordan, January 2008–February 2014. Issue 2 (29th January 2016) - Al‐Abdallat, Mohammad; Dawson, Patrick; Haddadin, Aktham Jeries; El‐Shoubary, Waleed; Dueger, Erica; Al‐Sanouri, Tarek; Said, Mayar M.; Talaat, Maha
Abstract : Background: Acute respiratory infections (ARIs) are a major cause of morbidity and mortality worldwide. Influenza typically contributes substantially to the burden of ARI, but only limited data are available on influenza activity and seasonality in Jordan. Methods: Syndromic case definitions were used to identify individuals with severe acute respiratory infections (SARI) admitted to four sentinel hospitals in Jordan. Demographic and clinical data were collected. Nasopharyngeal and oropharyngeal swabs were tested for influenza using real‐time reverse transcription polymerase chain reaction and typed as influenza A or B, with influenza A further subtyped. Results: From January 2008–February 2014, 2891 SARI cases were tested for influenza, and 257 (9%) were positive. While 73% of all SARI cases were under 5 years of age, only 57% of influenza‐positive cases were under 5 years of age. Eight (3%) influenza‐positive cases died. An annual seasonal pattern of influenza activity was observed. The proportion of influenza‐positive cases peaked during November–January (14–42%) in the non‐pandemic years. Conclusions: Influenza is associated with substantial morbidity and mortality in Jordan. The seasonal pattern of influenza aligns with known Northern Hemisphere seasonality. Further characterization of the clinical and financial burden of influenza in Jordan will be critical in supporting decisions regarding disease control activities.